Corporate Entrepreneur Actions dan Keunggulan Kompetitif: Studi pada aplikasi mobile banking “Jawara Mobile” Bank Banten - Cendria Tj. Tasdik; Ratih Purbasari; Margo Purnomo (Entrepreneurship Faculty, Universitas Garut, 2022)
The development of digital banking in recent years has experienced very significant growth. To be able to compete competitively with competitors in the digital banking market, it is necessary to have a corporate entrepreneur role in the digital baking business at Bank Banten which gives birth to mobile champion products by prioritizing competitive advantage. Jawara Mobile is a mobile banking application owned by Bank Banten. Jawara Mobile is a mobile application that is integrated in smartphones based on Android and iOS operating systems. This study uses a qualitative approach to create descriptive information in the form of written words from the observed object. The results of the study show competitive advantages based on operational excellence, product leadership and customer intimacy from Jawara Mobile Perkembangan digital banking dalam beberapa tahun terakhir mengalami pertumbuhan yang sangat signifikan. Untuk dapat bersaing kompetitif dengan competitor dalam pasar digital banking, diperlukan peranan corporate entrepreneur dalam bisnis digital baking pada Bank Banten yang melahirkan produk jawara mobile dengan mengutamakan keuanggulan kompetitif. Jawara mobile adalah aplikasi mobile banking milik Bank Banten. Jawara mobile adalah aplikasi mobile yang terintegrasi di smartphone berbasis sistem operasi Android dan iOS. Penelitian ini memakai pendekatan kualitatif guna menciptakan informasi deskriptif berbentuk kata - kata tertulis dari objek yang diamati. Hasil dari penelitian menunjukkan keunggulan kompetitif berdasarkan keunggulan operasional, kepemimpinan produk dan keakraban dengan nasabah produk dari jawara mobile